Hubungan Usia Menarche Dengan Perilaku Personal Hygiene Remaja Putri di Pondok Pesantren Al-Falah Sofwaniyah Jatirokeh - Fitriliana, Dea Riskha; Meikawati, Pedvin Ratna (JURNAL KESEHATAN TERAPAN, 2024)
Menarche is defined as the first menstruation, namely the discharge of blood from a woman's genitals in the form of the shedding of the inner wall lining of the uterus which contains many blood vessels. The aim of the research was to determine the relationship between the age of menarche and the behavior of young women at the Al-Falah Sofwaniyah Jatirokeh Islamic Boarding School. Method: The research method used is analytical observation, with a cross sectional research design. This research was carried out at the Al - Falah Sofwaniyah Jatirokeh Islamic Boarding School in 2023. The population of this research was located at the Al - Falah Sofwaniyah Jatirokeh Islamic Boarding School, namely all 38 teenagers. The sample from this research was 24 teenagers from the Al-Falah Sofwaniyah Jatirokeh Islamic Boarding School who had reached menarche. The sampling technique uses purposive sampling. Results: that respondents aged 11 years at menarche and who had bad behavior in dealing with menstruation were 2 people (9%) and those who had good behavior were 22 people (91%) of the total respondents. There were 12 respondents (50%) who had menarche aged 12 years and who had good behavior in dealing with menstruation and 2 people (9%) of the total respondents who had bad behavior. Respondents aged 13 years at menarche had good behavior in dealing with menstruation, namely 10 people (41%). The results of the Pearson correlation test obtained a P value = 0.001 < 0.05. Conclusion: There is a relationship between the age of menarche and the personal hygiene behavior of adolescents. The older a person is at menarche, the more likely they are to have good behavior in dealing with menstruation. On the other hand, the younger a person's age at menarche, the more likely they are to have bad behavior when dealing with menstruation.